1991
DOI: 10.1111/j.1365-2621.1991.tb05263.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Optimal Level of Lactitol for Surimi

Abstract: Cryoprotective effects of lactitol dihydrate at 2, 4, 6 and 8% levels in cod surimi were investigated and compared to an industrial control (1:l mixture of sucrose/sorbitol at 8% w/w) and to a control without additive. Stability of protein functional properties was monitored by salt extractable protein and differential scanning calorimetry analyses, as well as texture profile analyses of cooked gels for surimi stored at -12°C for 8 wk. Data revealed the excellent cryoprotective properties of lactitol. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…t p of myosin of WBM samples mixed with maltose varied significantly (P < 0.05) as a function of the mass fraction of trehalose and as a function of time (Table 3) (Herrera et al 2001). These shifts in t p of myosin to higher values as the mass fraction of trehalose and maltose increases can be interpreted as stabilisation of myofibrillar proteins since a higher temperature is required to denature these proteins (Sych et al 1990(Sych et al , 1991. The highest shift in myosin t p was shown by the samples of WBM mixed with 10% of trehalose for all storage time intervals.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 98%
See 1 more Smart Citation
“…t p of myosin of WBM samples mixed with maltose varied significantly (P < 0.05) as a function of the mass fraction of trehalose and as a function of time (Table 3) (Herrera et al 2001). These shifts in t p of myosin to higher values as the mass fraction of trehalose and maltose increases can be interpreted as stabilisation of myofibrillar proteins since a higher temperature is required to denature these proteins (Sych et al 1990(Sych et al , 1991. The highest shift in myosin t p was shown by the samples of WBM mixed with 10% of trehalose for all storage time intervals.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 98%
“…Myofibrillar protein denaturation during frozen storage expressed by the loss of protein solubility is a result of hydrogen or hydrophobic bonds formation, as well as of that of disulfide bonds, and of ionic interactions (Sych et al 1990(Sych et al , 1991MacDonald & Lanier 1991;Auh et al 1999). SEP of WBM decreased quasi linearly as a function of storage time.…”
Section: Salt Soluble Proteins (Sep)mentioning
confidence: 99%
“…Analysis of variance of myosin T p showed that myosin's T p varied significantly (P<0.05) as a function of mass fraction of trehalose, but not as of frozen storage time (Sych et al 1990;Herrera et al 2001) (Table 1). These shifts in T p of myosin to the higher values as the mass fraction of trehalose increases can be interpreted as a stabilization of myofibrillar proteins since a higher temperature was required to denature these proteins (Sych et al 1990;Sych et al 1991). Highest shift in T p of myosin shows the samples of WCM mixed with 10% of trehalose for all storage time intervals.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…T p of actin transitions vary significantly (P<0.05) with addition of trehalose but not with frozen storage time (Table 1). T p of myosin shows higher shift by increase of mass fraction of trehalose then a T p of actin for all samples and all time intervals (Table 1) (Sych et al 1990;Sych et al 1991). The method of expressing peak enthalpies ΔH was adopted to provide an estimate of the quantity of native proteins.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation